PENERAPAN PRINSIP 5C DALAM PEMBERIAN KREDIT SEBAGAI PERLINDUNGAN BANK - Niniek Wahyuni (Lex Journal: Kajian Hukum & Keadilan, 2017)
Provision of credit to the Debtor's customers may result in loss or risk to the bank as the creditor if the underlying matters are ignored. To gain confidence and protect the interests of the bank, the bank must make a careful assessment of the nature, capability, capital, collateral, and business prospects of the debtor's customers, known as "5C". But in practice, the application of the 5C principle analysis has not been implemented maximally, even though there is a tendency of banks to provide ease of requirements to the debtor's customers, because of the target that must be fulfilled by the bank.